Produção e qualidade de morangos a partir de formulações de fertilizantes alternativos - Vignolo, Gerson Kleinick (2011)
The effect of different fertilization formulations in pre-planting on yield and quality were evaluated for Camarosa and Camino Real strawberry cultivars (Fragaria x ananassa Duch.). This research was conducted at private farm located at Gama Road, 9th District of Pelotas / RS, during May to December 2009. The Camarosa and Camino Real strawberry cultivars were planted in annual system, using plant spacing of 0.30 x 0.30 m under low tunnels and drip irrigation. The treatments were based on doses of NPK (kg ha-1) recommended for strawberry crop. A factorial experiment arranged in a split-plot design was used, with two strawberry cultivars as main plot treatments, and ten levels of pre-planting fertilization as subplot treatments, with four replications. The experimental design was randomized blocks each replication consisted of 12 plants. The first six treatment were applied a fixed rate of castor bean (TM), phosphorite alvorada (FA) and potassium chloride (KCl) at 2400 kg ha-1, 375 kg ha-1 and 100 kg ha-1, respectively combined to: A1: 500 kg ha-1 MBR 7, A2: 1000 kg ha-1 MBR 7, A3: 1500 kg ha-1 MBR7, A4: 500 kg ha-1 MBR 33, A5: 1000 kg ha-1 MBR 33, A6: 1500 kg ha-1 MBR 33. The next four treatments were applied just TM, FA and KCl at three rates: A7: 0 kg ha-1 TM, 0 kg ha-1 FA and 0 kg ha-1 of KCl, A8: 800 kg ha-1 TM, 125 kg ha-1 FA and 33 kg ha-1 of KCl (1/3 of the recommended dose), A9: 1600 kg ha-1 TM, 250 kg ha-1 FA and 67 kg ha-1 KCl (2/3 of the recommended dose), A10: 2400 kg ha-1 TM, 375 kg ha-1 FA and 100 kg ha-1 of KCl (recommended). Data were analyzed by analysis of variance and mean comparison was determined by Tukey test at 5% probability and regression analysis was also used to determine treatments effects. Yield, harvest dynamics, physical and chemical fruit‟s properties, the flowering period of fruit maturation, dry shoot weight, chlorophyll index, soil and foliar chemical analysis were done. Camarosa cultivar showed a greater number of fruits and fruit weight per plant, greater dry shoot weight, TSS and TA, but lower TSS / TTA than 'Camino Real'. Camino Real cultivar had the largest average fruit weight besides fruit diameter and length, and higher chlorophyll index. Regarding the formulation of pre-planting fertilization, greater number of fruits occurred in A6 compared to A7 treatment. A2, A5 and A6 fertilization treatment resulted in a greater fruit weight than the control (A7). The fertilization rates of pre-planting which resulted in a greater number and fruit weight per plant were 1937 kg ha-1 and 1713 kg ha-1, respectively. The application of the three MBR 7 doses provided higher TSS when compared to A8 and A9 treatment.